Social support, psychosocial risks, and cardiovascular health: Using harmonized data from the Jackson Heart Study, Mediators of Atherosclerosis in South Asians Living in America Study, and Multi-Ethnic Study of Atherosclerosis - Jee Won Park; Chanelle J. Howe; Laura A. Dionne; Matthew M. Scarpaci; Belinda L. Needham; Mario Sims; Alka M. Kanaya; Namratha R. Kandula; Joseph L. Fava; Eric B. Loucks; Charles B. Eaton; Akilah J. Dulin (Elsevier, 2022)
Purpose: Social support may have benefits on cardiovascular health (CVH). CVH is evaluated using seven important metrics (Life's Simple 7; LS7) established by the American Heart Association (e.g., smoking, diet). However, evidence from longitudinal studies is limited and inconsistent. The objective of this study is to examine the longitudinal relationship between social support and CVH, and assess whether psychosocial risks (e.g., anger and stress) modify the relationship in a racially/ethnically diverse population. Methods: Participants from three harmonized cohort studies - Jackson Heart Study, Mediators of Atherosclerosis in South Asians Living in America, and Multi-Ethnic Study of Atherosclerosis - were included. Repeated-measures modified Poisson regression models were used to examine the overall relationship between social support (in tertiles) and CVH (LS7 metric), and to assess for effect modification by psychosocial risk. Results: Among 7724 participants, those with high (versus low) social support had an adjusted prevalence ratio (aPR) and 95% confidence interval (CI) for ideal or intermediate (versus poor) CVH of 0.99 (0.96-1.03). For medium (versus low) social support, the aPR (95% CI) was 1.01 (0.98-1.05). There was evidence for modification by employment and anger. Those with medium (versus low) social support had an aPR (95% CI) of 1.04 (0.99-1.10) among unemployed or low anger participants. Corresponding results for employed or high anger participants were 0.99 (0.94-1.03) and 0.97 (0.91-1.03), respectively. Conclusion: Overall, we observed no strong evidence for an association between social support and CVH. However, some psychosocial risks may be modifiers. Prospective studies are needed to assess the social support-CVH relationship by psychosocial risks in racially/ethnically diverse populations.